(untitled) (Experimental biology, 2016)
The binding of miRNAs with mRNAs of genes involved in the development of various subtypes of human lung cancer was studied. A computer program predicted miRNAs binding sites with genes mRNAs with high reliability was developed. The program calculates the ratio of ΔG/ΔGm, the reliability value, the location of the microRNA binding site in the 5’-untranslated region (5’UTR), in the protein coding portion (CDS) or in the 3’untranslated region (3’UTR). A search of miRNAs target genes was calculated with the MirTarget program. It was created a database of genes involved in the development of lung squamous cell carcinoma and large cell carcinoma. It were identified miRNAs which effectively bind to mRNAs of target gene. It were established associations of specific miRNAs with mRNAs of genes increased and reduced-expressed in squamous cell lung cancer. Among the miRNAs involved in the associations with mRNAs, the largest number of target genes was found for unique miRNAs: miR-1273g-3p, miR-1273h-5p, miR-1273f, miR-1322, miR-1285-5p, miR-619-5p. The obtained results of the effect of miRNAs on the expression of genes involved in oncogenesis may serve as a basis for the development of early diagnosis methods of lung cancer subtypes.